Myrmecophaga tridactyla (Pilosa: Myrmecophagidae) - Gaudin, Timothy (2018)
The monospecific giant anteater, Myrmecophaga tridactyla Linnaeus, 1758, is the largest of the 4 species of New World vermilinguans. A feeding specialist on ants and termites, it occupies a broad range of lowland habitats, from dry scrub and savannah to rainforests. Its geographic range extends throughout southern Central America and northern South America, from Honduras in the north to Bolivia and northern Argentina in the south. M. tridactyla is listed on Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) and is identified as " Vulnerable " on the International Union for Conservation of Nature and Natural Resources Red List.